Validity of guided inquiry-based chemical equilibrium e-module integrated with the Al-Quran for Madrasyah Aliyah - Haura Habiba; Iryani Iryani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This study aims to determine the validity of the guided inquiry-based chemical equilibrium e-module integrated with Al-Quran for class XI Madrasyah Aliyah. The type of research is developmental research (Educational Design Research) using the Plomp development model, which consists of a preliminary research stage, a prototype stage, and a field test. The research instrument used was a validation questionnaire comprised of a content validation questionnaire and a media validation questionnaire. The content validation questionnaire assessment was carried out by material expert validators consisting of Padang State University Chemistry Lecturers and MAN 2 Padang Teachers. The media validation questionnaire assessment was carried out by media expert validators consisting of Padang State University Chemistry and Informatics Engineering Lecturers. Based on the results of processing the media and content validation questionnaire data using the Aiken V formula, the average value of content validation is 0.88 in the valid category, and the media validation average value is 0.91 in the valid category.